2005
DOI: 10.1121/1.4778975
|View full text |Cite
|
Sign up to set email alerts
|

Acoustics of excited jets—a historical perspective

Abstract: The idea that a jet may be excited by an external forcing is not new. The first demonstration of a jet responding to external pressure waves occurred in the late 1800s. It was not, however, until the 1950s, with the advent of commercial jet aircraft, that interest in the subject greatly increased. Researchers first used excited jets to study the structure of the jet and attempt to determine the nature of the noise sources. The jet actuators of the time limited the range (size and Mach number) of jets could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The pronounced sensitivity of jets to variations of the inflow condition has been demonstrated experimentally 13,14 as well as numerically. 15,16 Hence, investigating the sensitivity of the simulations to changes in disturbance amplitudes seems appropriate.…”
Section: Introductionmentioning
confidence: 83%
“…The pronounced sensitivity of jets to variations of the inflow condition has been demonstrated experimentally 13,14 as well as numerically. 15,16 Hence, investigating the sensitivity of the simulations to changes in disturbance amplitudes seems appropriate.…”
Section: Introductionmentioning
confidence: 83%
“…Apart from the direct propagation of core noise to the far field, core noise fluctuations can play a pivotal role in the jet noise amplification. 4 Experimental studies have shown that tonal and broadband excitations upstream of the nozzle exit can amplify the jet noise by as much as 5-10 dB compared to the unforced condition. [5][6][7] In particular, Bechert & Pfizenmaier 7,8 reported a pronounced broadband shift of the radiated sound for excitations at the preferred shear-layer frequency.…”
Section: Introductionmentioning
confidence: 99%